(3JWhjQ GdcJGH GdeOQSj (B: (3eMJhi cJGH GdYdhe GddZhjI fehPLGs - (3eSde, YeQs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2007)
(3jJfGhd GdHMK ehVhY JWhjQ eMJhi cJGH GddZI GdYQHjI aj GdJYdje GdYGe, ajWQM eSCdI GdfMh GdYQHj hOdGdGJg hhXjaJg aj VHW ChGNQ GdcdeGJ, heMGQHI GddMf HGddZI, heSCdI JjSjQ YedjI GdfMh GdYQHj aj GdeOGQS(B. (3cPdc jQqcR GdHMK Ydi JHhjH GdeSGFd GddZhjI aj cJH GdfMh GdeOQSjI GdJj JNU GdJdGejP hdjS GdeJNUUjf HGddZI(B. (3haj gPG GdSjGb jSJYQV gPG GdHMK LghO GdChGFd ef GdSda aj JHhjH ehVhYGJ GdfMh hGdUQa, Ke jfJbd Edi LghO GdagQSI hGdJHhjH YfO GdeMOKjf(B. (3hjWGd GdHMK CjVkG HGdJbjje JLQHI hVY cJH LOjOI ddZI GdYQHjI aj GdefgL GdJYdjej GdadSWjfj hGdJj CXgQJ JLGhHkG cGedkG ef hRGQI GdJQHjI GdadSWjfjI, jbGHdg ehba SdHj ef LGfH eDdaj GdcJH ef GdeNJUjf HGddZI GdYQHjI CfaSge(B. (3hjNdU GdHMK Edi VQhQI GYJeGO fehPL ehMO dJHhjH GdeSGFd GddZhjI aj cJH GdbhGYO GdYQHjI(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Enseignement des langues Livres Scolaires; Teaching languages Textbooks; (3JYdje GddZGJ GdcJGH GdeOQSjs